PENGEMBANGAN MEDIA POP-UP BOOK DIGITAL BERBASIS CONTEXTUAL TEACHING AND LEARNING PADA PEMBELAJARAN IPAS SISWA KELAS IV SD NEGERI 29 LUBUKLINGGAU - Dahlia, Fitria; Valen, Andri; Andita, Cahyo Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to produce a digital pop-up book media product based on contextual teaching and learning in science learning for fourth-grade students at SD Negeri 29 Lubuklinggau that meets the criteria for validity, practicality, and effectiveness. The research method used was research and development (R&D) with the ADDIE development model. The subjects were 23 fourth-grade students. Data collection techniques included observation, interviews, questionnaires, and tests. The results showed that the CTL-based digital pop-up book media was declared valid based on expert assessments, with an Aiken's V coefficient of 0.87 for media experts, 0.93 for language experts, and 0.98 for material experts, categorizing it as high. The results of the practicality analysis for teachers and students met the criteria for practicality, with an average score of 91.53%. Furthermore, the effectiveness analysis obtained an N-gain of 0.72, categorizing it as high. Therefore, it can be concluded that the CTL-based digital pop-up book media in science learning meets the criteria for validity, practicality, and effectiveness and can therefore be used in learning.